Supervising doctoral candidates - Rolph, Chris (Surviving and thriving in academia, 2024)
Early career faculty colleagues may only recently have completed their own doctoral studies, and what knowledge they have of supervising doctoral candidates may be limited. Supervising Doctoral Candidates provides support for new and young academics who, from the beginning of their academic career, may be expected to support doctoral candidates with little or no prior training. Each chapter draws on the more extensive experience of international authors, providing encouragement and gentle advice on the role of the supervisor and the relationships with the student and co-supervisors as the doctoral study progresses. The structure of the book follows the student's journey - from selecting an appropriate topic of study, through the support needed to develop research skills and begin writing, to publications and the final defence of the thesis. Understanding the needs of doctoral candidates, developing relationships with other supervisors, and how to work with non-academic members of the supervising team are covered in this collection, with consideration given to different types of students including those with disabilities and those who join from abroad. Delivering practical and useful mentorship advice grounded in lived experience, Supervising Doctoral Candidates assists early-career academics and addresses the challenges of supervision.